Air Pollution with Asbestos Fibers in Some Heavy Traffic Areas of Baghdad - Ajeel, Nahla Sh.; Fleeh , Nada A.; Sultan, Matham A. (Iraqi Journal of Science, 2021)
This research was conducted to measure the levels of asbestos fibers in the air of some dense sites of Baghdad city, which were monitored in autumn 2019. Samples collection was conducted via directing air flow to a mixed cellulose ester membrane filter mounted on an open‑faced filter holder using sniffer with a low flow sampling pump. Air samples were collected from four studied areas selected in some high traffic areas of Baghdad city, two of them were located in Karkh (Al-Bayaa and Al-Shurta tunnel) and two in Rusafa (Al-Jadriya and Al-Meshin complex), then analyzed to determine concentrations of asbestos. Measuring of levels of asbestos fibers on the filters was carried out via using scanning electron microscope SEM together with an energy dispersive X‑ray system (EDS). The results showed that the lowest level was recorded in Al-Jadriya intersection (0.0352 fiber/ml), while the maximum concentration was in Al-Bayaa (0.156 f/ml). Asbestos average concentration in the ambient air of the four studied areas was 0.0718 f/ml, which exceeded the standards of world health organization (WHO) for air which is equal to 0.0022 f/ml. This may be due to the presence of crowded traffic and the occurrence of industries near the city. Therefore, plans such as management of traffic, changing locations of industrial sites, and products substitution can be effective in minimizing the concentrations of airborne fibers.